Descriptions of two new species of the leafhopper genus Idioscopus Baker (Hemiptera: Cicadellidae: Eurymelinae: Idiocerini) from China - Guo, Meishu; Dai, Renhuai (Zootaxa, 2025)
Two new species of the leafhopper genus Idioscopus Baker, I. triprocessus sp. nov. and I. xanthomacula sp. nov., are described and illustrated from China. I. myrica Wang & Dai, 2018 is placed as a junior synonym of I. bimaculatus (Pruthi, 1936) syn. nov. A checklist and key to species of Idioscopus Baker from China are provided.